Bird sightings checklist, winter 1978-1979 - Iowa Ornithologists' Unionet al (1978)
Bird sightings checklist, winter 1978-1979. Includes handwritten annotations with locations and weather information. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Field Report of winter 1978-1979. Epson - sheet feed/flatbed